Girard's mimetic theory across the disciplines - Cowdell, Scott; Fleming, Chris; Hodge, Joel (New York Continuum International Publishing Group, 2012)
Showcases the application of Rene Girard's mimetic theory across a range of disciplines, including philosophy, religious studies, literature and cultural studies.
Keywords: Girard, Rene -- 1923-2015 -- Philosophy; Philosophy, Modern -- 20th century; Violence; Imitation; Desire; Religion